2015
DOI: 10.1121/1.4934551
|View full text |Cite
|
Sign up to set email alerts
|

The role of prosody in infants' early syntactic analysis and grammatical categorization

Abstract: This study tested the hypothesis that phrasal prosody assists early syntactic acquisition. Stimulus-sentences consisting of French determiners and pseudo-lexical-words were ambiguous between two syntactic structures, e.g., [[TonDet felliAdj craleN]NP [vurV laDet gosineN]VP] versus [[TonDet felliN]NP [craleV vurPrep laDet gosineN]VP], which had distinct prosodic cues. French-learning 20-month-olds were familiarized with the sentences either in the prosody of one structure, or the other structure. All infants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Very recent studies in French suggest that such a mechanism for language acquisition is plausible: 2-year-olds were shown to exploit suprasegmental information from phrasal prosody to correctly identify noun-verb homophones, 20 and 18-month-olds were shown to use this suprasegmental information to interpret novel words as either nouns or verbs, depending on their position within the prosodic-syntactic structure of the sentence. 21,22 These recent findings in French, along with our current results in English, lend support to the hypothesis that phrasal prosody cues syntactic structure in early language development, and likely in different languages. Previous difficulties detecting this connection were likely due to the fact that the link between prosodic and syntactic structure was not sufficiently systematic in the structures that were tested.…”
Section: Discussionsupporting
confidence: 71%
“…Very recent studies in French suggest that such a mechanism for language acquisition is plausible: 2-year-olds were shown to exploit suprasegmental information from phrasal prosody to correctly identify noun-verb homophones, 20 and 18-month-olds were shown to use this suprasegmental information to interpret novel words as either nouns or verbs, depending on their position within the prosodic-syntactic structure of the sentence. 21,22 These recent findings in French, along with our current results in English, lend support to the hypothesis that phrasal prosody cues syntactic structure in early language development, and likely in different languages. Previous difficulties detecting this connection were likely due to the fact that the link between prosodic and syntactic structure was not sufficiently systematic in the structures that were tested.…”
Section: Discussionsupporting
confidence: 71%
“…Many studies confirm the early role of prosody in children’s syntactic analysis (e.g. Carvalho, Dautriche, & Christophe, 2016; Christophe, Millotte, Bernal, & Lidz, 2008; Demuth, 2018; Gerken, 1994; Massicotte-Laforge & Shi, 2015; Shady et al, 1995) for initial construction of a developmental theory in which a convergence of FCs with phrasal prosody may underlie syntactic acquisition (e.g. a Prosodic Licensing Hypothesis).…”
Section: Resultsmentioning
confidence: 94%
“…Infants discriminated and preferred grammatical sentences, where the target word appeared in a syntactically appropriate context, demonstrating an integration of FCs and sentential context (Cauvet, Limissuri, Millotte, Margules, & Christophe, 2010). In another study, French-learning toddlers between 17 and 24 months of age demonstrated abstract sentence-based computation involved in their access and use of FCs (Massicotte-Laforge & Shi, 2015). Twenty-month-old infants were familiarized with either crale as NP ([ Ton felli crale ][ vure la gosine ]) or as verb phrase ([ Ton felli ][ crale vure la gosine ]), depending only on the syntactic and prosodic analysis in the examples (all words except the determiners are nonsense forms).…”
Section: Infants and Fcsmentioning
confidence: 99%
“…Newborns are able to exploit rhythmic information to discriminate between languages (Mehler et al, 1988;Nazzi, Bertoncini, & Mehler, 1998); from 4.5 months onwards, infants are sensitive to the coherence of prosodic constituents (Gerken, Jusczyk, & Mandel, 1994;Hirsh-Pasek et al, 1987;Jusczyk, Hohne, & Mandel, 1995;Männel & Friederici, 2009;Soderstrom, Seidl, Nelson, & Jusczyk, 2003), they show better recognition and memory for segments that correspond to whole prosodic units than for those which span prosodic boundaries (Mandel, Jusczyk, & Nelson, 1994;Nazzi, Iakimova, Bertoncini, Frédonie, & Alcantara, 2006) and they can rely on prosodic cues to segment the speech stream into words and constrain their lexical access (Gout, Christophe, & Morgan, 2004;Johnson, 2008;Millotte et al, 2010;Shukla, White, & Aslin, 2011). All of these findings, together with the reliable relationship between prosodic and syntactic structures, suggest that toddlers might be able to use phrasal prosody, not only to facilitate memory and lexical access, but also to constrain their syntactic analysis (see Christophe et al, 2008;Hawthorne & Gerken, 2014;Massicotte-Laforge & Shi, 2015;Morgan & Demuth, 1996;Morgan, 1986;Shi, 2014).…”
Section: Introductionmentioning
confidence: 99%